Novel Soy β-Conglycinin Core-Shell Nanoparticles As Outstanding Ecofriendly Nanocarriers for Curcumin - Liu, Ling-Ling; Liu, Peng-Zhan; Li, Xiu-Ting; Zhang, Ning; Tang, Chuan-He (Journal of agricultural and food chemistry, 2019)
The development of high-performance nanocarriers for nutraceuticals or drugs has become one of the topical research subjects in the functional food fields. In this work, we for the first time propose a novel and ecofriendly process to obtain a kind of nanostructured soy β-conglycinin (β-CG; a major soy storage globulin) as outstanding nanocarriers for poorly soluble bioactives (e.g., curcumin), by a urea-assisted disassembly and reassembly strategy. At urea concentrations > 4 M, the structure of β-CG gradually dissociated into its separate subunits (α, α', and β) and even denatured (depending on the type of subunits); after dialysis to remove urea, the dissociated subunits would reassemble into a kind of core-shell nanostructured particles, in which aggregated β-subunits acted as the core while the shell layer was mainly composed of α- and α'-subunits. The core-shell nanoparticles were favorably formed at protein concentrations of 1.0-2.0 wt %. Curcumin crystals were directly introduced into the β-CG solution at high urea concentrations (e.g., 8 M) and would preferentially interact with the denatured β-subunits. As a consequence, almost all of the curcumin molecules were encapsulated in the core part of the reassembled core-shell nanoparticles. The loading amount of curcumin in these nanoparticles could reach 18 g of curcumin per 100 g of protein, which far exceeds those reported previously. The encapsulated curcumin exhibited a high water solubility, extraordinary thermal stability, and improved bioaccessibility, as well as a sustained release behavior. The findings provide a novel strategy to fabricate a kind of high-encapsulation-performance, organic solvent-free, and biocompatible nanocarrier for hydrophobic nutraceuticals and drugs.